The Tato.Net Initiative – A Program Developed by the Cyryl and Metody Foundation in Support of Contemporary Fatherhood - Patrycja Kaszubska-Dziergas (Paedagogia Christiana, 2024)
This study aims to present the operation of the Tato.Net Initiative [Dad.Net] implemented by the Cyryl and Metody Foundation (hereafter referred to as the Foundation). The programme was launched in 2004 to promote conscious and responsible fatherhood among contemporary men through self-education and self-formation amidst a crisis in masculinity, brought on by modern civilisation, and its negative consequences with regard to fatherhood. The Tato.Net programme implements initiatives and projects to strengthen families through the empowering presence of the father, both in the physical and spiritual sense. The programme also engages in cooperation with social organisations and institutions that similarly advance the culture of responsible fatherhood. All actions undertaken by Tato.Net reflect the idea of fatherhood, with the project itself founded on two primary values: the empowerment of a family by the presence of the father and the promotion of a culture of responsible fatherhood. The paper presents different projects executed by the Foundation in a few countries.